PENGEMBANGAN MEDIA PEMBELAJARAN GAME “TRADEQUEST” MATERI PERDAGANGAN INTERNASIONAL IPS KELAS 8 SMP - Johandi Rahma Rafani; Fatiya Rosyida; Johandi Rahma Rafani (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2024)
Abstract: In providing the best learning, teachers must have good and professional competence in providing learning such as understanding students, using innovative media, and providing learning that suits students' interests. This research aims to develop RPGM game-based learning media called Trade Quest: International Trade in international trade material for grade 8 middle school. Learning media was developed using the ADDIE development model which contains procedures in the form of Analysis, Design, Development, Implementation and Evaluation. The resulting media can be opened on students' computers or smartphones. The results of the media evaluation show that the media is suitable for use with revisions and the implementation results show that students are enthusiastic and interested in using the learning media TradeQuest: International Trade